O fantástico feminino na busca do real: desdobramentos da manifestação do gênero na contística de Júlia Lopes de Almeida e de Augusta Faro - Brezolin, Alana (My University, 2023)
This dissertation understands to what extent the manifestation of the fantastic is altered, in terms of its inscriptions of the real, in the short stories "A casa dos mortos", by Júlia Lopes de Almeida (1862-1934), published in the press in 1893 and integrating the collection Ânsia eterna, released in 1903; and "As flores", by Augusta Faro (1948-), which makes up the collection A friagem, published in 1998. This is done in view of the yearning of fantastic literature to seek the or approach the real, since, according to the Spanish theorist David Roas (2011, 2014), the goal of the fantastic is to reflect and question reality and its limits, destabilizing them. This study intends, therefore, to argue that the fantastic is not opposed to the real, as we perceive the yearning of fantastic literature to seek the or approach the real. We consider it more appropriate to state that the fantastic contrasts with the real rather than opposes it. Even though all fiction has a support in reality, we intend to emphasize that the fantastic also depends on the reality to sustain itself, since, due to the presence of the supernatural, the fantastic may seem more fictional or less realistic than other narratives. This will be demonstrated in Brazilian fantastic literature written by women, by two writers who present the fantastic with great mastery: Júlia Lopes de Almeida and Augusta Faro. Both, however, in the construction of the Brazilian historiographical narrative, were either placed in the background or silenced: the former, despite having been an important and internationally recognized 19th century writer, and the latter, although having a relevant allegorical prose in the 20th and 21st centuries. The research takes as theoretical support, among others, the discussions of Murilo Garcia Gabrielli (2004), Karla Menezes Lopes Niels (2018) and Bruno Anselmi Matangrano and Enéias Tavares (2019), on Brazilian fantastic literature; Constância Lima Duarte (1997), Zahidé Lupinacci Muzart (1997), Roberto Reis (1992) and Lúcia Osana Zolin (2009), on literature by women authors and their relations with the canon; Tzvetan Todorov (2017), Irène Bessière (2012), Jaime Alazraki (1990) and David Roas (2011, 2014), on fantastic literature; Roberto Reis (1980) and David Roas (2011, 2014), on the inscriptions of the real; and Francisco Vicente de Paula Junior (2011), David Roas (2020) and Ana Paula dos Santos Martins (2021), on the female fantastic. The results point to the evolution of fantastic literature, from "A casa dos mortos" (2019), by Júlia Lopes de Almeida to "As flores" (2001), by Augusta Faro. In addition, show that both short stories present inscriptions of the real, in which not only real elements constitute the texts, but these are built in order to demonstrate that they function as the real. [resumo fornecido pelo autor]
Esta dissertação compreende em que medida se altera a manifestação do fantástico, no que tange às inscrições do real nele, nos contos "A casa dos mortos", de Júlia Lopes de Almeida (1862-1934), publicado na imprensa em 1893 e presente na coletânea Ânsia eterna, lançada em 1903; e "As flores", de Augusta Faro (1948-), que compõe a coletânea A friagem, publicada no ano de 1998, tendo em vista o anseio da literatura fantástica em buscar o ou se aproximar do real, uma vez que, segundo o teórico espanhol David Roas (2011, 2014), o objetivo do fantástico é refletir e questionar sobre a realidade e seus limites, desestabilizando-os. Este estudo pretende, portanto, defender que o fantástico não se opõe ao real, porque percebemos o anseio da literatura fantástica em buscar o ou se aproximar do real. Consideramos mais adequado afirmar que o fantástico se contrasta com o real do que se opõe a ele. Ainda que toda a ficção tenha um amparo no real, visamos ressaltar que o fantástico também depende do real para se sustentar, visto que, pela presença do sobrenatural, o fantástico possa parecer mais ficcional ou menos realista do que outras narrativas. Isso será demonstrado na literatura fantástica brasileira de autoria feminina, de duas escritoras que apresentam com grande maestria o fantástico: Júlia Lopes de Almeida e Augusta Faro. Ambas, contudo, na construção da narrativa historiográfica brasileira, ou foram postas em segundo plano, ou silenciadas: a primeira, apesar de ter sido uma importante escritora do século XIX, reconhecida internacionalmente, e, a segunda, ainda que conte com uma relevante prosa alegórica do século XX e XXI. A pesquisa toma como suporte teórico, entre outras, as discussões de Murilo Garcia Gabrielli (2004), Karla Menezes Lopes Niels (2018) e Bruno Anselmi Matangrano e Enéias Tavares (2019), sobre a literatura fantástica brasileira; Constância Lima Duarte (1997), Zahidé Lupinacci Muzart (1997), Roberto Reis (1992) e Lúcia Osana Zolin (2009), sobre a literatura de autoria feminina e suas relações com o cânone; Tzvetan Todorov (2017), Irène Bessière (2012), Jaime Alazraki (1990) e David Roas (2011, 2014), sobre a teoria da literatura fantástica; Roberto Reis (1980) e David Roas (2011, 2014), sobre as inscrições do real; e Francisco Vicente de Paula Júnior (2011), David Roas (2020) e Ana Paula dos Santos Martins (2021), sobre o fantástico feminino. Os resultados apontam para a evolução da literatura fantástica, de "A casa dos mortos" (2019), de Júlia Lopes de Almeida a "As flores" (2001), de Augusta Faro. Além disso, mostram que ambos os contos apresentam inscrições do real, em que não só elementos reais constituem os textos, pois as narrativas também estão construídas a fim de demonstrar que funcionam como o real. [resumo fornecido pelo autor]
Keywords: Literatura fantástica - Crítica e interpretação; Literatura fantástica brasileira - Crítica e interpretação; Escritoras brasileiras; Almeida, Júlia Lopes de, 1862-1934; Faro, Augusta, 1948-; Fantasy literature - Criticism and interpretation; Brazilian fantasy literature - Criticism and interpretation; Women authors, Brazilian